Mathematical Modeling of Interrelationship Analysis to Determine Multi-Criteria Decision Making Casual Relations - Aghelie, Amir; Sorooshian, Shahryar; Noor Azlinna, Azizan (Akademi Baru, 2016)

(untitled)
Abstract: The Multi Criteria Decision Making (MCDM) delivers strong decision making in areas where selection of best alternative is highly complex. This paper reviews and explain the main condensations of MCDM models and practices in detail. The purpose is explained and identify various application and the approaches and to suggests different MCDM models for different decision makling issues and how to select the best alternatives. This paper also examines the DEMATEL model and problems in DEMATEL for decision making and how DEMATEL have been improved to overcome the problems. The MCDM methods have helped to choose the best alternatives where that they are many criteria are present, the best can be selected and analyzed the different scope for the criteria, weights for the criteria and the choose the ideal ones using any multi criteria decision making methods.